The Influence of Chemical and Mineral Compositions on the Parameterization of Immersion Freezing by Volcanic Ash Particles. Issue 17 (8th September 2021) - Umo, N. S.; Ullrich, R.; Maters, E. C.; Steinke, I.; Benker, N.; Höhler, K.; Wagner, R.; Weidler, P. G.; Hoshyaripour, G. A.; Kiselev, A.; Kueppers, U.; Kandler, K.; et al.
Abstract: Volcanic ash (VA) from explosive eruptions contributes to aerosol loadings in the atmosphere. Aside from the negative impact of VA on air quality and aviation, these particles can alter the optical and microphysical properties of clouds by triggering ice formation, thereby influencing precipitation and climate. Depending on the volcano and eruption style, VA displays a wide range of different physical, chemical, and mineralogical properties. Here, we present a unique data set on the ice nucleation activity of 15 VA samples obtained from different volcanoes worldwide. The ice nucleation activities of these samples were studied in the Aerosol Interaction and Dynamics in the Atmosphere (AIDA) cloud simulation chamber as well as with the Ice Nucleation Spectrometer of the Karlsruhe Institute of Technology (INSEKT). All VA particles nucleated ice in the immersion freezing mode from 263 to 238K with ice nucleation active site (INAS) densities ranging from ∼10 5 to 10 11 m −2, respectively. The variabilities observed among the VA samples, at any given temperature, range over 3.5 orders of magnitude. The ice‐nucleating abilities of VA samples correlate to varying degrees with their bulk pyroxene and plagioclase contents as a function of temperature. We combined our new data set with existing literature data to develop an improved ice nucleation parameterization for natural VA in the immersion freezing mode. This should be useful for modeling the impact of VA on clouds. Plain Language Summary: Volcanic ash particles, which are generated during volcanic eruptions, can initiate ice formation in clouds. The clouds formed by these volcanic ash particles can influence precipitation, and in turn, weather and climate. In our study, we investigated the ability with which volcanic ash particles form ice in clouds. We performed our study in a state‐of‐the‐art aerosol and cloud simulation chamber and on a cold‐stage instrument. The findings show that volcanic ash particles can form ice as effectively as mineral dust particles or their components. These results will help scientists to have a better understanding of the impact of volcanic ash particles on clouds. Key Points: The ice‐nucleating ability of natural volcanic ash particles in the immersion freezing mode can vary by 3.5 orders of magnitude Ice‐nucleating properties of volcanic ash particles correlate to varying degrees with their pyroxene and plagioclase contents The temperature‐dependent immersion freezing ability of volcanic ash is approximated with an exponential fit line